NILAI-NILAI PENDIDIKAN DALAM IBADAH PUASA (Studi Anilasis terhadap Surat Al-Baqarah Ayat 183-187) - Taufik Mukmin (El-Ghiroh : Jurnal Studi Keislaman, 2017)
From the results of the study, it can be concluded that fasting is to refrain from eating, drinking, and sexual relations and to withhold from the things that break the fast since the time of dawn until sunset with the intent to train and refrain from its passions and desires contrary with the rules of fasting in order to form a private cautious and obey the rules of Allah. As for other forms of educational values ​​embodied in the fasting is to educate honesty, fasting educates hard work, fasting educates for discipline, fasting teaches patience, fasting teaches gratitude, fasting educates equality, fasting educate people to always learn and seek knowledge and fasting educate empathy.